2016
DOI: 10.1134/s0965544116030063
|View full text |Cite
|
Sign up to set email alerts
|

Triptane synthesis from methanol and dimethyl ether: A review

Abstract: The review summarizes and analyzes the results of research in the field of triptane synthesis from methanol and dimethyl ether (DME). The reaction with a fairly high triptane yield occurs in the presence of both homogeneous and heterogeneous catalysts. It has been shown that InI 3 and ZnI 2 are the most com monly used catalysts for the homogeneous process, while zeolite systems based on H BEA and H Y are promising catalysts for the heterogeneous process. The effect of the catalyst nature (acidity and structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Triptane (2,2,3-trimethylbutane) is the most valuable high-octane component of gasoline among C 5 –C 8 -isoparaffin hydrocarbons. Due to its highly branched structure and high octane number of 112, triptane is particularly effective for replacing aromatics in fuels. Currently, there is no acceptable method of its production that could be recommended for industrial implementation, due to the low values of dimethyl ether conversion and triptane yield …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triptane (2,2,3-trimethylbutane) is the most valuable high-octane component of gasoline among C 5 –C 8 -isoparaffin hydrocarbons. Due to its highly branched structure and high octane number of 112, triptane is particularly effective for replacing aromatics in fuels. Currently, there is no acceptable method of its production that could be recommended for industrial implementation, due to the low values of dimethyl ether conversion and triptane yield …”
Section: Introductionmentioning
confidence: 99%
“…10−14 Currently, there is no acceptable method of its production that could be recommended for industrial implementation, due to the low values of dimethyl ether conversion and triptane yield. 14 Few studies devoted to the synthesis of triptane from oxygenates (methanol and dimethyl ether) were carried out mainly under conditions of homogeneous catalysis at a temperature of 175−200 °C in the presence of predominantly zinc and indium halides. 15−20 In comparison with metal halides, solid catalysts do not cause equipment corrosion and make it possible to simplify the separation of reaction products and the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Units designed for conversion of natural gas into olefins through a methanol intermediate are gradually being put into operation. The units of the following companies are functioning: ExxonMobil (United States), UOP (United States), Lurgi (Germany), Sinopec (China) [10]. In connection with the wide use of zeolites in the above-mentioned processes and modern approach to conversion of a number of organic substances into hydrocarbons, it is necessary to be able to develop catalysts with a definite set of properties; to monitor their selectivity, efficiency, and activity during the reaction; and to control deactivation, which is one of the main problems for zeolite catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al theoretically demonstrated two reaction pathways for the methylation of olefins with ketene, that is, direct association and sequential dissociation pathways . Methylation was also observed in the direct syngas conversion to aromatics over OXZEO catalysts, where benzene, toluene, and xylenes (BTX) were methylated on the acid sites in the pore-mouth region or on external surfaces of H-ZSM-5 forming C 9+ aromatic compounds. , This understanding successfully led to the synthesis of tetramethylbenzene in syngas conversion over the OXZEO catalysts. , It was also reported that in the conversion of methanol and dimethyl ether (DME), olefins (C n ) can be methylated to larger iso-olefins (C n +1 ), and the mono-branched iso-olefins (C n +1 ) can be methylated to di-branched (C n +2 ) and tri-branched iso-olefins (C n +3 ) over different zeolites, such as MFI, MOR, FAU, and BEA. The correlation between the ratio of iso/ n -paraffins and the ratio of olefins/paraffins in Figure S5 also indicates to some extent the importance of olefin methylation in the formation of isoparaffins. More olefins will facilitate the methylation reaction, resulting in a higher ratio of iso/ n -paraffins.…”
mentioning
confidence: 99%